The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s00276-001-0061-7
|View full text |Cite
|
Sign up to set email alerts
|

An accessory flexor digitorum longus muscle with high division of the tibial nerve

Abstract: An accessory flexor digitorum longus muscle associated with a high division of the tibial nerve was encountered during routine dissection in the right leg of a newborn cadaver. The tibial nerve divided into its two terminal branches at a higher level than normal with a small branch from the tibial nerve contributing to one of the terminal branches. In addition, an accessory flexor digitorum longus muscle was observed to pass between the terminal branches of the tibial nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Kurtoglu et al stated that a high division of the tibial nerve was associated with an accessory flexor digitorum muscle [18]. We did not come across such findings but probably a larger sample size can help in better evaluation of this.…”
Section: Discussionmentioning
confidence: 67%
“…Kurtoglu et al stated that a high division of the tibial nerve was associated with an accessory flexor digitorum muscle [18]. We did not come across such findings but probably a larger sample size can help in better evaluation of this.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, a bilateral anomalous extended origin of the soleus muscle has been reported by Barberini et al (2003). Cases of accessory flexor digitorum longus muscle are also been reported in the literature (Gumusalan and Kalaycioglu, 2000;Kurtoglu et al, 2001). Gurbuz et al (1999) have reported a case an unusual muscle on the medial side of the flexor hallucis longus, on its lower distal half.…”
mentioning
confidence: 84%
“…This muscular anomaly has numerous variables regarding its origin site: tibia, fibula, posterior muscle septum, the leg's fascia profunda, and posterior muscular compartment. There are also variations regarding volume and extension (Turner, 1867;Wood, 1868;Macalister, 1875;Testut, 1884;Driver & Denison, 1914;Lewis;Nathan et al, 1975;Nidecker et al, 1984;Bergman et al, 1988;Erickson et al;Sammarco & Stephens;Buckingham et al;del Sol et al;Gümüs¸alan & Kalayciog˘lu, 2000;Kurtoglu et al;Jaijesh et al 2006;Athavale et al, 2012). This muscle was first described by Meckel (Testut;Hwang & Hill, 2009 Sooriakumaran & Sivananthan;Georgiev et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Anatomical variations in the distal portion of the leg and ankle are infrequent, but if these are present they become important from the morphological point of view and their influence in the clinical sphere (Lewis, 1962;Erickson et al, 1990;Sammarco & Stephens, 1990;Yüksel et al, 1993;Buckingham et al, 1997;del Sol et al, 2000;Kurtoglu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%